2021
DOI: 10.21203/rs.3.rs-1111734/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Comparative Study of the Nonlinear Methods for Estimate Body Weight by Body Measurements on Different Sample Sizes in Morkaraman Sheeps

Abstract: The objective of this study was to estimate body weight of Morkaraman sheeps from body measurements with nonlinear models. Selected 110 sheeps 3-5 years were scored for body weight, body length, height at wither, chest width and pump width. For determine relationships with body weight between body measurements, correlation analysis was performed. The results of the correlation analysis indicated that the highest relationship according to the all sample sizes were body weight between body length (0.95, 0.90, 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Contrary to this, other studies found that LW is correlated with different body measurements depending on the sex of the lambs [23]. WH and BL are other body measurements that have been found to be highly correlated with LW [30,31].…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Contrary to this, other studies found that LW is correlated with different body measurements depending on the sex of the lambs [23]. WH and BL are other body measurements that have been found to be highly correlated with LW [30,31].…”
Section: Discussionmentioning
confidence: 59%
“…In this regard, using the exponential model, Canul-Solís et al [33] estimated the live weight of Pelibuey ewes from hip width with a similar precision to that found in the present study. Another study showed that with small sample sizes (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), logistic and saturation growth models can be used to determine the LW of Morkaraman sheep using BL as a predictor, and with sample sizes bigger than 20, incomplete gamma is the most accurate model [31].…”
Section: Discussionmentioning
confidence: 99%